PEMERIKSAAN TOKSIKOLOGI PADA KASUS BUNUH DIRI DENGAN ASAM KLORIDA DAN TINJAUAN ASPEK MEDIKOLEGAL - Edwin Tambunan; Ahmad Yudianto (Masyarakat Hukum Kesehatan Indonesia, 2022)
Suicide is an unnatural way of dying. The prevalence of suicide is still high in several countries, including Indonesia. Based on data from the Indonesian Ministry of Health, in Indonesia, there are more than 16,000 suicides every year. The following is a report of a suicide case that was autopsied at Bhayangkara Hospital and carried out for toxicological examination. At the crime scene, a plastic bottle containing a cloudy blue liquid was found around the victim. The results of the laboratory examination of the gastric samples taken during the autopsy and the plastic bottles showed that they contained hydrochloric acid. Article 133, paragraph 1 of the Criminal Code explains that there is a need for good cooperation between investigators and forensic doctors to determine the cause of death. Forensic laboratory examination is very helpful in determining the cause of death